Scientific assessment of ozone depletion : 2010. Executive Summary (World Meteorological Organization GenevaCH, 2011)
This document contains key summaries from the Scientific Assessement of Ozone Depletion : 2010. This summarised scientific assessment is the latest in a series of eleven scientific assessments prepared by the world's leading experts in the atmospheric sciences and under the international auspices of the World Meteorological Organization and/or the United Nations Environment Programme.
Keywords: OZONE